Analisis Perbandingan Nilai Gizi Nugget Ikan Tuna Fortifikasi Wortel dan Jagung: Comparative Nutritional Analysis of Tuna Nuggets Fortified with Carrot (Daucus carota) and Corn (Zea mays) - ravika mutiara; Putri Welhelmina; Ida Suryani; Sri hajriani; Nurul Muchlizah Z; Mariani H. Mansur; Marliana S (Depertemen Teknologi Pertanian Universitas Hasanuddin, 2026)
Nuggets are generally made from chicken meat. However, with technological advancements, various processed variants such as beef and fish have been developed. Tuna fish is a type of fish that can be utilized as the raw material for nugget production. Nevertheless, efforts are required to enhance its nutritional value through the addition of corn or carrots. This study aims to analyze the comparison of nutritional values in tuna nuggets using three treatments: A (350 g tuna without fortification), B (350 g tuna + 250 g corn), and C (350 g tuna + 250 g carrots). This research employs quantitative data based on a positivistic approach (concrete data). Proximate analysis was conducted to compare tuna nuggets fortified with corn and those fortified with carrots. Results indicate that the highest moisture content was found in treatment C (57.76%). The highest protein content was observed in treatment A (31.66%), and the highest fat content was also in treatment A (4.22%). Overall, fortification with carrots and corn improves the functional nutritional profile, despite reducing protein and fat levels, resulting in nuggets with lower fat and higher moisture. The product complies with SNI 01-6688-2001 standards and is recommended for diversification of fish-based food products.